Coping styles and lifestyle factors among hypertensive and non-hypertensive subjects - Fadzil, Mohd Ariff; Ariaratnam, Suthahar; Musa, Ramli (Singapore Medical Association, 2011)
Introduction: The objective of this study was to investigate the relationship between hypertensive patients and their coping style and associated lifestyle factors. Methods: A total of 502 participants attending nine outpatient clinics completed the validated Bahasa Malaysia version of the Coping Inventory for Stressful Situations and sociodemographic questionnaires. The height, weight, pulse rate and blood pressure of all the participants were measured using standardised methods. Results: A total of 264 (52.6 percent) participants were hypertensive, while 238 (47.4 percent) were not. Participants with a high task-oriented score showed a significantly lower risk of hypertension compared to those with a low score (odds ratio [OR] 0.546; 95 percent confidence interval [CI] 0.371–0.804). Those with a high emotion-oriented coping score were associated with an increased risk of hypertension (OR 1.691; 95 percent CI 1.107–2.582). Hypertension was also significantly associated with a higher mean body mass index, positive family history of hypertension, history of diabetes mellitus and hypercholesterolaemia. In multiple logistic regression analysis with hypertension status as the dependent variable, a high emotion-oriented coping score, a low taskoriented coping score, age, body mass index, positive family history of hypertension and history of diabetes mellitus remain significant factors in the final model. Conclusion: These results indicated a significant relationship between hypertension and coping styles and lifestyle factors. They underscored the importance of further study as well as the development and implementation of intervention measures to improve coping skills among hypertensive patients, which may be incorporated into the management of hypertension.